Peran Digital Entrepreneurship Mindset: Keputusan Adopsi Platform Digital Bagi Pelaku Bisnis - Dewi Widyaningsih; Edwin Zusrony; Hardi Utomo (Diponegoro University, 2023)
The research was conducted to analyze the influence of developing a digital entrepreneurship mindset as an impact of facing digital transformation for MSME actors by considering digital aptitude factors, digital literacy. Non-random sampling techniques were taken by 120 MSME actors and questionnaire distribution techniques by convenience sampling. Data analysis method to determine the relationship between variables with multiple linear regression and path analysis test (sobel test), data was processed using the IMB SPSS 25 application. Finding the results of digital aptitude t count 5,531 and digital literacy tcount 4,419 > ttable1,980 (level sig. 5%) have a significant effect on DEM and all simultaneous variables 47% influence the development of digital entrepreneurship mindset. Digital aptitude tcount 5,531 and digital literacy tcount 3,215> 1,980 have a significant effect on digital platform adoption decisions and variables simultaneously by 55% have an influence on adopting digital platforms. Meanwhile, the results of the DEM pathway test were significantly able to mediate the influence of digital aptitude Zhitung = 2 and digital literacy Zhitung = 2.854> 1.96 on digital platform adoption decisions.